Introducing learning models focusing on elementary school science activity in terms of a systemic literature review - Rahmadina, Annisa; Rohmani, Rohmani; Haryadi, Rofiq Noorman (Journal of Science and Education (JSE), 2024)
Education is an effort made by individuals to follow the learning process. Implementing and selecting the appropriate learning model is critical to achieving ideal learning success. This study examines learning models for increasing science learning activities in elementary schools. The research method applied in this study is the Systematic Literature Review (SLR). This systematic approach allows us to investigate and synthesize the latest research findings in primary school learning. The data obtained comes from literature studies using the PRISMA approach through the stages of identification, screening, eligibility, and Inclusion. The data came from the Google Scholar or Google Cendikia databases, with the research time range covering the last six years, from 2018 to 2023. The results of this study obtained a database with the keywords Learning Model AND Science Learning Activity AND Elementary School Students. the results were selected, and ten articles were taken that met the inclusion criteria for analysis. To achieve the best possible learning success for students, implementing suitable learning models in scientific instruction in primary schools can positively affect their learning activities. It is recommended that further research be able to describe more learning models in increasing science learning activities in students in elementary schools.